Transfer lengths and bond strengths for composites bonded to concrete - Bizindavyi, L.; Neale, K. W.
An effective method for strengthening existing concrete beams in bending consists in bonding fiber-reinforced composite laminates on the tension faces of the beams. Laboratory tests on beam specimens show, however, that it is often difficult to develop the full composite strength capacity because of premature failure due to delamination and peeling-off of the laminate. Conditions at the interface between the composite and concrete are not yet fully understood, and studies are required to determine the development lengths needed to achieve the composite's strength capacity. In this paper, we report results of an experimental and theoretical investigation of composite-to-concrete bonded joints. We first present a new and fairly simple experimental apparatus designed and constructed in our laboratory. With this test rig it is possible to investigate the shear conditions between the composite and concrete, to determine the stress and strain distribution profiles in a composite laminate that is bonded to the concrete, and to make direct measurements of the bond strengths. A brief description of the apparatus is given and experimental results are presented. A theoretical analysis for the behavior of such composite-to-concrete bonded joints has also been developed. Predictions of the numerical model are compared to the experimental results.
Keywords: BENDING (DEFORMATION); BOND STRENGTH (MATERIALS); CONCRETE BEAMS AND GIRDERS; DELAMINATIONINTERFACES (MATERIALS); LAMINATED COMPOSITES; MATHEMATICAL MODELS; PEELING; STRAIN; STRESS CONCENTRATION; STRUCTURAL ANALYSIS